STRATEGI PEMASARAN OLAHRAGA DI ERA DIGITAL : MENGOPTIMALKAN MEDIA SOCIAL UNTUK MENJANGKAU AUDIEN BARU - Dindin Abidin; Asep Setiawan; Rizka Putra; Aghus Jamaludin Kharis; Pito Fernando; Iriana Bakti (EDU RESEARCH, 2024)
The development of digital technology has changed the sports marketing landscape. Social media has become one of the effective marketing tools to reach new audiences and increase sports fan engagement. This research aims to analyse sports marketing strategies in the digital era by optimising the use of social media. The research method used is a literature study and case analysis of several sports organisations that successfully utilise social media in their marketing strategies. Data was collected from various sources such as scientific journals, articles, and official websites of sports organisations. The results show that social media offers many opportunities for sports organisations to connect with a wider audience, build brand awareness, and increase fan engagement and loyalty. Effective sports marketing strategies in the digital age include the use of engaging multimedia content, the utilisation of influencers and brand ambassadors, and data analysis to understand audience preferences. In addition, collaboration with social media platforms can also increase the reach and visibility of sports content. The conclusion of this study is that social media has become an important marketing tool for sports organisations to reach new audiences and increase fan engagement in the digital age. Sports organisations need to design marketing strategies that are integrated with social media to achieve effective marketing goals.